21st century geography : a reference handbook - Stoltman, Joseph P. (Thousand Oaks, Calif. : SAGE Publications, 2012)
Via approximately 80 entries the SAGE 21st Century Reference Series volumes on geography will highlight the most important topics, issues, questions, and debates any student obtaining a degree in this field ought to have mastered for effectiveness in the 21st century. --from publisher description
v. 1. Physical and environmental geography -- Human geography -- v. 2. Nature and society -- Regions and regional perspectives -- Geographic information science -- Applied and professional geography.
Includes bibliographical references and index.
Keywords: Geography -- Handbooks, manuals, etc